2022
DOI: 10.1590/s1980-65742022010121
|View full text |Cite
|
Sign up to set email alerts
|

Acute caffeine and capsaicin supplementation and performance in resistance training

Abstract: This study aimed to evaluate the acute supplementation effects of capsaicin, caffeine, and the combined capsaicin plus caffeine on total volume (total repetitions x weight lifted), rate of perceived exertion (RPE), and side-effects on resistance training. Methods: Eleven men (21.5 ± 2.1 years, 1.75 ± 0.08 m, 79.64 ± 10.1 kg), trained in resistance training (experience of 4.5 ± 2.6 years, weekly frequency 5 ± 0.8 days) were recruited. This was a crossover, randomized, double-blind study. Each volunteer went thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 29 publications
6
32
0
Order By: Relevance
“…Six studies were excluded because they were performed using animal models or did not evaluate endurance performance. Thus, 13 studies were found to satisfy the inclusion criteria in the first phase [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 ]. In the second phase, an additional 532 search results were found, and one study satisfied the inclusion criteria [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies were excluded because they were performed using animal models or did not evaluate endurance performance. Thus, 13 studies were found to satisfy the inclusion criteria in the first phase [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 ]. In the second phase, an additional 532 search results were found, and one study satisfied the inclusion criteria [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, r amounted to 0.90 and therefore this value was used for all studies in the aerobic endurance analysis. For the analysis of muscular endurance, correlation was calculated using the individual data from two studies [ 20 , 23 ]. In these two studies, correlation values were 0.65 and 0.93.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations